Exploring the heavy metal ion sequestration ability of gum copal‐collagen hybrid based interpenetrating polymer network: Kinetics, isotherms, and biodegradation studies. (12th August 2020) - Kaur, Savneet; Jindal, Rajeev
Abstract: In this article, gum copal‐collagen hybrid based interpenetrating polymeric network (IPN) [(GcA‐coll)‐cl‐poly(AAm‐ip‐AA)] has been used as a green adsorbent for the removal of Pb(II) and Cd(II) from waste water. Adsorption equilibrium was achieved in 9 h and pseudo‐second‐order model was found to be the closest fit to the kinetic adsorption data. Freundlich adsorption isotherm model was found to closely match with the sorption behavior of Pb(II) and Cd(II). The reaction parameters like initial metal ion concentration, adsorbent dose, pH, and the reaction time were optimized to get the hydrogel with maximum metal ion removal capacity (91.65% for Pb(II) and 95% for Cd(II)). The maximum percentage biodegradation of IPN was 80.25% by the compositing method. This IPN is an efficient, low cost potential adsorbent with excellent biodegradation and can act as an environment‐friendly agent for removing heavy metals from water. Abstract :